The First Principle of Supervision in Endowment - A Jurisprudential and Legal Analysis - غلامرضا یزدانی; سیدمحمدحسن موسوی خراسانی; ام البنین مقتدایی (پژوهش‌های فقهی مسائل مستحدثه)
Supervision in endowments (waqf) is divided into two types: exploratory and advisory. The purpose of exploratory supervision is to become informed about matters related to the endowed property in endowments. In this type of supervision, there is no need for the trustee to consult with the supervisor regarding the affairs of the endowment; whereas, in advisory supervision, the supervisor, with their intervening role, is responsible for carrying out the affairs, and the trustee must seek the supervisor's opinion before taking any action. Since the primary principle of supervision, in the absence of explicit instructions from the endower regarding the supervisor's performance, is not specified in any legal or jurisprudential texts, the question arises as to what type of supervision applies in such a case. This is because, on one hand, the lack of clarity regarding the type may prevent the endower's objectives from being realized, and on the other hand, it may lead to disputes over the responsibilities of the trustee and the supervisor. This research, which is based on a descriptive-analytical method, addresses the issue that due to the alignment of advisory supervision with the philosophy of oversight, prevention of prolonged litigation, and the determination of the endowment's interests, this type of supervision is compatible with the optimal conduct of individuals and helps prevent wrongdoing while favoring caution; as it can be aligned with the principle of the relationship between ruling and subject and analogy.